2016
DOI: 10.1371/journal.pone.0156807
|View full text |Cite|
|
Sign up to set email alerts
|

Pyrosequencing Unveils Cystic Fibrosis Lung Microbiome Differences Associated with a Severe Lung Function Decline

Abstract: Chronic airway infection is a hallmark feature of cystic fibrosis (CF) disease. In the present study, sputum samples from CF patients were collected and characterized by 16S rRNA gene-targeted approach, to assess how lung microbiota composition changes following a severe decline in lung function. In particular, we compared the airway microbiota of two groups of patients with CF, i.e. patients with a substantial decline in their lung function (SD) and patients with a stable lung function (S). The two groups sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 54 publications
(68 reference statements)
2
19
0
2
Order By: Relevance
“…Thus, the recognition of a diverse and complex community inhabiting the lower airways proved enticing 24. Cross-sectional cohort studies have demonstrated patients with advanced lung disease are more likely to have microbial communities with limited diversity, dominated by classical CF pathogens 25. However, predictive studies are required to understand if the microbiome may be harnessed to predict clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the recognition of a diverse and complex community inhabiting the lower airways proved enticing 24. Cross-sectional cohort studies have demonstrated patients with advanced lung disease are more likely to have microbial communities with limited diversity, dominated by classical CF pathogens 25. However, predictive studies are required to understand if the microbiome may be harnessed to predict clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant bacterial species in CF, such as P. aeruginosa [69] and Staphylococcus aureus [70,71], possess large, flexible gene pools, including genes encoding antibiotic resistance, pathogenicity, environmental response, and metabolic flexibility, which may explain the adaptive nature of chronic infections [72]. Although the metagenome contributes greatly to interactions with the host [25,73], very few studies on CF metagenomes have been performed, involving a limited number of both patients [29,63,74,75] and specific metabolic functions [76]. By analyzing the abundance of specific genes, such studies found a homogeneous distribution of predicted bacterial community activities (e.g., specific metabolic pathways) across patients with similar pulmonary function, as indicated by forced expiratory volume in 1 second (FEV 1 ) [73], suggesting a relationship between microbiome function and clinical status.…”
Section: Many Singers But Which Song(s)?mentioning
confidence: 99%
“…It may be possible to tailor therapeutic interventions considering the entire microbiome, including the microbial taxa present, their abundances, and the nature of their interactions with each other and with the host. Deciphering the intimate interactions within the microbiome and the 'ecosystem service' it provides to the holobiont (the 'song' referred to previously [77]) could lead to identification of keystone functions and taxa and allow for the maintenance of a healthy respiratory microbiome [75]. Moreover, in a holobiont framework, considering the data already collected on the gut-lung axis [115], it may be reasonable to hypothesize that manipulation of the airway and gut microbiomes through dietary intervention, probiotic cocktails, CFTR modulators, or others therapeutic interventions (like vitamin D supplementation, sodium chloride supplementation, or antioxidant vitamin intake), could synergize with antimicrobial treatment and may be used for designing personalized precision approaches for prevention as well as treatment of CF lung disease.…”
Section: Clinician's Cornermentioning
confidence: 99%
“…Pseudomonas aeruginosa is a common and dominant pathogen found in the airways of both CF and non-CF bronchiectasis patients [9][10][11][12][13]. Chronic infection has been associated with more severe decline in lung function [14][15][16][17][18][19], increased hospitalizations [20,21], frequent exacerbations [22] and disease severity [23,24].…”
Section: Microbiologymentioning
confidence: 99%